KARAKTERISTIK FILM PELAPIS PANGAN DARI SURIMI BELUT SAWAH DAN TAPIOKA [Charateristics of Edible Film from Field Eel Surimi and Tapioca Starch] - Budi Santoso; . Herpandi; Vemi Ariani; Rindit Pambayun (Jurnal Teknologi dan Industri Pangan, 2013)
The objective of this research was to determine the characteristics of edible film made of surimi rice field eel and tapioca starch. The treatments consisted of surimi rice field eel concentrations of of 4, 6, and 8 (% v/v) and tapioca starch concentrations (1, 3, and 5 b/v). The experiment was arranged in a Factorial Randomized Block Design with two factors as treatments, and each combination for the treatment was carried out in triplicates. The results showed that surimi concentration, tapioca concentration and interaction between the two treatments significantly affected (at 5% level test) the water activity, thickness, pressure strength, tensile strength, percentage of elongation, and water vapor transmission rate. The best edible film was made of 6% of surimi concentration and 3% of tapioca concentration. The characteristics of the edible film were water activity of 0.27; thickness of 0.11 mm; pressure strength of 6.51 N/m2; tensile strength of 10.46 N/m2; percent elongation of 32%; and water vapor transmission rate of 6.77 g.m-2.24 hour -1.